Highly Efficient and Stable Saline Water Electrolysis Enabled by Self‐Supported Nickel‐Iron Phosphosulfide Nanotubes With Heterointerfaces and Under‐Coordinated Metal Active Sites. (13th July 2022) - Yu, Zhipeng; Li, Yifan; Martin‐Diaconescu, Vlad; Simonelli, Laura; Ruiz Esquius, Jonathan; Amorim, Isilda; Araujo, Ana; Meng, Lijian; Faria, Joaquim Luis; Liu, Lifeng
Abstract: Direct seawater electrolysis is proposed as a potential low‐cost approach to green hydrogen production, taking advantage of the vastly available seawater and large‐scale offshore renewable energy being deployed. However, developing efficient, earth‐abundant electrocatalysts that can survive under harsh corrosive conditions for a long time is still a significant technical challenge. Herein, the fabrication of a self‐supported nickel‐iron phosphosulfide (NiFeSP) nanotube array electrode through a two‐step sulfurization/phosphorization approach is reported. The as‐obtained NiFeSP nanotubes comprise abundant NiFeS/NiFeP heterointerfaces and under‐coordinated metal sites, exhibiting outstanding activity and durability for the hydrogen and oxygen evolution reactions (HER and OER) in simulated alkaline‐seawater solution (KOH + NaCl), with an overpotential of 380 (HER) and 260 mV (OER) at 500 mA cm ‐2 and outstanding durability of 1000 h. Theoretical calculations support the observed outstanding performance, showing that the heterointerface and under‐coordinated metal sites synergistically lower the energy barrier of the rate‐determining step reactions. The NiFeSP electrode also shows good catalytic performance for the urea oxidation reaction (UOR). By coupling UOR with HER, the bifunctional NiFeSP electrode pair can efficiently catalyze the overall urea‐mediated alkaline‐saline water electrolysis at 500 mA cm ‐2 under 1.938 V for 1000 h without notable performance degradation. Abstract : A self‐supported NiFeSP nanotube array electrode combining several advantages including multiple metal/non‐metal components, 3D hierarchical architecture, and abundant heterointerfaces and under‐coordinated active sites, is fabricated and shows outstanding electrocatalytic performance for hydrogen evolution, oxygen evolution, and urea oxidation reactions at high current densities, demonstrating a great potential for use in practical energy‐saving saline water electrolysis.